Transhepatic stent placement for malignant portal vein obstruction: Long term efficacy and factors associated with stent failure. Issue 149 (April 2022) - Ju Kim, Yong; Jin Yoon, Chang; Hwan Lee, Jae; Seok Choi, Won; Yoon, Yoo-Seok; Hwang, Jin-Hyeok; Kim, Jaihwan
Abstract: Purpose: To evaluate the long-term efficacy of transhepatic stent placement in patients with symptomatic malignant portal vein (PV) obstruction and to identify risk factors for stent failure. Methods: From April 2011 to March 2021, transhepatic stent placement was attempted in 36 patients with symptomatic malignant PV obstruction: naïve (n = 20) or recurrent tumor after surgery (n = 16). Technical success, clinical outcomes, and complications were retrospectively evaluated. Thirteen relevant variables were analyzed to determine risk factors for stent failure. Results: Stent was successfully placed in all but one patient (97.2%, 35/36). Thromboaspiration (n = 9) and jejunal variceal embolization (n = 4) were performed in same session. Symptoms related to portal hypertension were resolved in 30 of the 35 patients (85.7%). There was no procedure-related major complication. During the follow-up period (median 175 days),  stent failures occurred in 8 patients (22.9%): 7 stent thromboses within 90 days and one tumor ingrowth at 715 days after stent placement. The 1-, 6-, 12-month stent patency was 94.1%, 78.2%, and 62.6%, respectively. In multivariate analysis, the presence of PV thrombosis at the time of stent placement was associated with stent failure (HR 7.22; 95% CI 1.26–41.29, p = 0.03). Conclusion: Transhepatic stent placement is a safe and effective treatment for malignant PV obstruction. However, stent failure was common (22.9%) and mostly due to early stent thrombosis. The stent failure was associated with PV thrombosis at the time of stent placement.